Life After Head and Neck Cancer: Navigating the Years Ahead. Issue 2 (3rd April 2022) - Fox, Suzette; Lewis, Greg
ABSTRACT: Although much has been written about the initial impact of head and neck cancer (HNC) and its disruptive effect on the quality of people's lives, less attention has been paid to treatment repercussions in survivorship and associated psychosocial issues. In response to this gap in the literature, cancer care social workers from a large inner-city hospital in Australia set out to qualitatively explore that phenomenon. A focus group was conducted in September 2016 with seven adult participants recruited from a well-established self-help support group of HNC survivors. Thematic analysis of the focus group discussion gives voice to the patient experience in the cancer journey. This new information can inform social work interventions to support people with the difficult repercussions of HNC and help them to move through deeply personal change processes. IMPLICATIONS Findings from this focus group study are a timely reminder of the need for social work interventions that build cancer survivors' coping capacity. Insights highlight the importance of psychoeducation and supportive counselling to assist patients and families deal with experiences of loss in the head and neck cancer survivorship journey.